Evaluation of the Level of Zinc and Malondialdehyde in Basal Cell Carcinoma - Ziba MAJIDI; Mahmoud DJALALI; Mohammad Hasan JAVANBAKHT; Mojtaba FATHI; Mahnaz ZAREI; Koorosh FOLADSAZ (Tehran University of Medical Sciences, 2017)
Background: Basal Cell Carcinoma (BCC) is one of the most common skin cancers in the world and that use to lifestyle, increasing chemical pollutions, environmental factors and poor nutrition. The most important cause of this cancer is oxidative stress and free radicals so antioxidant activities for the body are so important. The aim of this study was to determine the variation of zinc and (Malondialdehyde) MDA in BCC patients. Methods: This study has been performed on case and control patients from 2013 to 2014. The samples were collected from cell carcinoma patients at Razi Hospital in Tehran, Iran. We evaluated the level of zinc with the use of Atomic Absorption Spectroscopy (AAS) method. Besides, we evaluated MDA with colorimetric assay. Results: The concentration of MDA was significantly higher in case group in comparison to control group (P=0.001). In addition, case group had lower concentration of zinc than the control group (P=0.000). There was no correlation between MDA and body mass index (BMI) and between zinc and BMI. Conclusion: All the patients with BCC showed a significant MDA serum in comparison with control group. However, significant decrease in zinc serum of the patients was seen that is because of consuming zinc during oxidative stress process so topical use of zinc in the form of 2+ ions could be effective on antioxidant protection against the sun UV radiation.